Analisis Kinerja Bundaran Duhung Di Kota Kuala Kurun Kabupaten Gunung Mas: Performance Analysis Of Duhung’s Roundabout In Kuala Kurun City Gunung Mas Regency - Andika, Andika; Murniati, Murniati; Laufried, Laufried (Media Ilmiah Teknik Sipil, 2021)
Changes in the volume of traffic passing through duhung roundabout have an impact on traffic conditions. This study aims to find out traffic volume, roundabout performance and road geometric shapes. The method used is MKJI 1997. Hasil analysis shows that the interlaces Bundaran Duhung in 2020 has the largest interlacess current value of 815 junior/hour on the AB interlace (Ahmad YaniStreet – Tjilik RiwutStreet), the largest capacity on the AB braid (Ahmad Yani Street -Jalan Tjilik Riwut),which is6803 junior/hour, with the highest saturation rate of cd braids (Jalan Kopri-Jalan Tjilik Riwut) which is0.274,the average roundabout traffic delay(DT R) is 2.07 det / smp, the average roundabout delay (DR) is 6.07 det / smp and includes the characteristics of service level in the current condition is class A. Geometric Duhung Roundabout has the largest value of -5,800%, on arm D (Jalan Tjilik Riwut), on arm A (Ahmad Yani Street) which is 2.824%, on arm B (Jalan Tjilik Riwut) which is 1.424%, on arm C (Kopri) which is -3.425%, from geometric research results of roundabout on arm D (Jalan Tjilik Riwut) does not meet the maximum limit of 4%, thus reducing the comfort of road users.